The Influence Of Customer Satisfaction And Price Reasonability In Building Customer Loyalty Of Logistics Service Companies - Kristiawan, Raditya Yogi; Abdi, Antonius Surjo (Kontigensi : Jurnal Ilmiah Manajemen, 2025)
-